2019
DOI: 10.1051/0004-6361/201834143
|View full text |Cite
|
Sign up to set email alerts
|

Second AGILE catalogue of gamma-ray sources

Abstract: Aims. We present the second AGILE-GRID Catalog (2AGL) of γ-ray sources in the 100 MeV -10 GeV energy range. Methods. With respect to previous AGILE-GRID catalogs, the current 2AGL Catalog is based on the first 2.3 years of science data from the AGILE mission (the so called 'pointing mode') and incorporates more data and several analysis improvements, including better calibrations at the event reconstruction level, an updated model for the Galactic diffuse γ-ray emission, a refined procedure for point-like sour… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 110 publications
0
20
0
Order By: Relevance
“…Several LSP blazars are not detected in the X-ray band, as the X-ray emission of this type of objects is weak and their flux may easily be below the sensitivity of currently available observations. For similar reasons, HSPs with relatively high ν peak values might not be de-Radio/Fermi Catalogs X-ray Catalogs NVSS (Condon et al, 1998) XMMSL Dr2 Clean (Saxton et al, 2008) FIRST (White et al, 1997;Helfand et al, 2015) 3XMM Dr8 (Watson et al, 2009) SUMSS V2.1 (Manch et al, 2003) RASS 2RXS (Boller et al, 2016) CRATES (Healey et al, 2007) WGACAT2 (White et al, 2000) Fermi 4FGL (The Fermi-LAT collaboration, 2019) Swift 1SXPS (Evans et al, 2014) Fermi 3FHL (The Fermi-LAT collaboration, 2017) SDS82 (Brandt and Giommi, 2019 in preparation) Fermi 3FGL (Acero et al, 2015) Einstein IPC (Harris et al, 1990) 1BIGB SED (Arsioli et al, 2018) Einstein IPC slew survey (Munz, 1992) MST-9Y (Campana et al, 2018) BMW-HRI (Panzera et al, 2003) FermiMeV (Principe et al, 2018) Chandra (Evans et al, 2010) 2AGILE (Bulgarelli et al, 2019) Swift OUSXB (Giommi et al, 2019) Swift OUSXG (Giommi et al, 2019 in preparation) Blazar/Pulsar/GRB/Quasar Catalogs Cluster of galaxies Catalogs 5BZCat (Massaro et al, 2015) ZW CLUSTERS (Zwicky et al, 1968) 3HSP (Chang et al, 2019) PLANCK SZ2 (Planck Collaboration, 2016) ATNF PULSAR (Manchester et al, 2005) ABELL (Abell et al, 1989) Fermi 2PSR (The Fermi-LAT Collaboration, 2013) MCXC (Piffaretti et al, 2011) Fermi GRB (Ajello et al, 2019) SDSS WHL (Wen et al, 2009) Million Quasar (Flesch, 2015) SW XCS (Liu et al, 2015) VO conesearch in this step is set to same as the input radius, same as in the first phase. The GALEX data then are converted to monochromatic fluxes and de-reddened using Fitzpatrick (1999) extinction rule.…”
Section: Workflowmentioning
confidence: 99%
See 1 more Smart Citation
“…Several LSP blazars are not detected in the X-ray band, as the X-ray emission of this type of objects is weak and their flux may easily be below the sensitivity of currently available observations. For similar reasons, HSPs with relatively high ν peak values might not be de-Radio/Fermi Catalogs X-ray Catalogs NVSS (Condon et al, 1998) XMMSL Dr2 Clean (Saxton et al, 2008) FIRST (White et al, 1997;Helfand et al, 2015) 3XMM Dr8 (Watson et al, 2009) SUMSS V2.1 (Manch et al, 2003) RASS 2RXS (Boller et al, 2016) CRATES (Healey et al, 2007) WGACAT2 (White et al, 2000) Fermi 4FGL (The Fermi-LAT collaboration, 2019) Swift 1SXPS (Evans et al, 2014) Fermi 3FHL (The Fermi-LAT collaboration, 2017) SDS82 (Brandt and Giommi, 2019 in preparation) Fermi 3FGL (Acero et al, 2015) Einstein IPC (Harris et al, 1990) 1BIGB SED (Arsioli et al, 2018) Einstein IPC slew survey (Munz, 1992) MST-9Y (Campana et al, 2018) BMW-HRI (Panzera et al, 2003) FermiMeV (Principe et al, 2018) Chandra (Evans et al, 2010) 2AGILE (Bulgarelli et al, 2019) Swift OUSXB (Giommi et al, 2019) Swift OUSXG (Giommi et al, 2019 in preparation) Blazar/Pulsar/GRB/Quasar Catalogs Cluster of galaxies Catalogs 5BZCat (Massaro et al, 2015) ZW CLUSTERS (Zwicky et al, 1968) 3HSP (Chang et al, 2019) PLANCK SZ2 (Planck Collaboration, 2016) ATNF PULSAR (Manchester et al, 2005) ABELL (Abell et al, 1989) Fermi 2PSR (The Fermi-LAT Collaboration, 2013) MCXC (Piffaretti et al, 2011) Fermi GRB (Ajello et al, 2019) SDSS WHL (Wen et al, 2009) Million Quasar (Flesch, 2015) SW XCS (Liu et al, 2015) VO conesearch in this step is set to same as the input radius, same as in the first phase. The GALEX data then are converted to monochromatic fluxes and de-reddened using Fitzpatrick (1999) extinction rule.…”
Section: Workflowmentioning
confidence: 99%
“…BAT 105 Months (Baumgartner et al, 2013) 10 acrmin γ-ray catalogs Search Radius (arc-minutes) Fermi 3FGL (Acero et al, 2015) 20 Fermi 2FHL (Ackermann et al, 2015) 20 Fermi 3FHL (The Fermi-LAT collaboration, 2017) 20 Fermi 4FGL (The Fermi-LAT collaboration, 2019) 20 1BIGB SED (Arsioli et al, 2018) 10 2AGILE (Bulgarelli et al, 2019) 50 Fermi MeV (Principe et al, 2018) 30 TeV/IACTs catalogs Search Radius (arc-minutes) MAGIC 10 VERITAS 10…”
mentioning
confidence: 99%
“…There are several other pieces of evidence as well which associate very high energy sources (MeV to TeV) to the surrounding star formation region of WR 121a (see Chaves et al 2008;Acero et al 2013;Rappoldi et al 2016;de Wilt et al 2017;H. E. S. S. Collaboration et al 2018;Bulgarelli et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the emission was twice as large in the post-periastron phase (Hamaguchi et al 2020). At higher energies, AGILE reported a substantially larger γ-ray flux before the periastron at 4σ above 100 MeV (Piano et al 2019), increasing by an order of magnitude with respect to the flux reported in the second AGILE-GRID catalogue (2AGL) of (1.81 ± 0.36) • 10 −7 photons cm −2 s −1 (Bulgarelli et al 2019). Contrarily, a Fermi-LAT analysis above 100 MeV during the same dates provides a flux of (1.42 ± 0.78) • 10 −7 photons cm −2 s −1 (T S = 2.4), thus consistent with the 2AGL result.…”
Section: Orbit-to-orbit Variabilitymentioning
confidence: 97%